Analisis Pengendalian Kualitas Produk Roti Tawar Menggunakan Metode Seven Tools Quality di UMKM Kiwus Coffee & Bakery - Ola rosita (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2026)
Kiwus Coffee & Bakery produces white bread and still faces quality inconsistency. This study identifies dominant defects, evaluates process stability, and formulates improvements using the Seven Quality Tools. A descriptive quantitative design was applied through observation, interviews, and documentation in August–September 2025. Data were collected from 20 batches with a constant sample of 32 loaves per batch, or 640 loaves. The check sheet recorded 37 defective products (5.8%). The defects were wrinkled crust, non-standard size, non-standard cutting, and hollow bread. Pareto analysis placed improvement priorities on non-standard cutting (32.43%), non-standard size (29.73%), and wrinkled crust (21.62%), with a cumulative contribution of 83.78%. The np-chart showed the process remained under control. Main causes were human, method, and machine factors; therefore, improvements should focus on SOPs, supervision, operator training, and tool maintenance